Riuh Birama: from the Malay Pencak Silat Tradition to the World Music Approach - Ramadhan, Viqrie; Hakim, Uswatul; Hidayat, Hengki Armez (Pascasarjana Institut Seni Indonesia Padang Panjang, 2024)
Malay Pencak Silat Melayu is a related Malay art known as classical Malay art which is often performed at receptions for grand guests or guests of honour. The development of Malay Pencak Silat performances can be found in the implementation of traditional Malay wedding ceremonies, events, circumcision events and events featuring regional arts, especially in Riau Province. Riuh Birama's musical composition was created using a World Music approach. The artist embodies ideas sourced from Malay Pencak Silat Accompaniment Music by developing melodic patterns using the Cengkok, Grenek, Patah techniques. The composition of Riuh Birama is realized in several stages, namely; 1) observation; 2) determining the concept; 3) material preparation; 4) discussion and commitment; and 5) embodiment. The creator tries to present several forms of novelty in the form of works following the concept being offered.